Peran Komunikasi Antarpribadi dalam mengatasi Perundungan pada Anak - Aulia Septihani; Doni Prasetyo Tri S.H; Elena Ayu Pramita; Dr. Yunita Sari, M.Si. (PT. Anagata Sembagi Education, 2024)
School bullying is a grave concern prevalent in both societal and educational realms. It encompasses negative actions perpetrated by one or more individuals aiming to harm, intimidate, or assert power over others, leading to physical, verbal, or psychological harm. As defined by Smith and Brain (2017), bullying constitutes a series of deliberate acts targeting individuals to inflict physical, verbal, or psychological distress. The distressing reality of bullying recently unfolded in an elementary school in Palembang, resulting in profound detrimental effects on the victims. This incident underscores the urgent need for comprehensive measures to address and prevent bullying in educational settings. It necessitates fostering a culture of empathy, respect, and inclusion, coupled with robust intervention strategies and support systems to safeguard the well-being of all students. Only through concerted efforts can schools ensure a safe and nurturing environment conducive to learning and personal growth